Pelatihan Praktek Hafalan Surah Pendek Dalam Kegiatan Festival Anak Sholeh Di Desa Lama Kecamatan Sei Lepan Kabupaten Langkat - Syahrul Kodrah; Rani Febriyanni; Syahrizal Amri; Novia Putri; Lily Aulia (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Community service (PKM) is one of the pillars of the Tri Dharma of Higher Education. One form of its realization is through cooperation between the regional government and universities in the form of implementing KKN which is sustainable and mutually beneficial. The purpose of this PKM is to improve children's competence, morals and manners, increase enthusiasm in learning Islamic religion, develop interests and talents and increase the creativity and self-confidence of children in the Old Village through the implementation of an activity program entitled "Children's Festival Saleh” (FAS) which was held by KKN STAI-JM Tanjung Pura students who were directly guided by Field Supervisors (DPL). The implementation of the Sholeh Children's Festival program consists of 3 activities, namely the call to prayer competition, a short letter memorization competition, and a Muslim fashion show competition. The implementation method applied to the pious children's festival program uses debriefing, training, and practice methods. The results of this PKM are that elementary school-age children are more enthusiastic and have basic Islamic knowledge, dare to show talent and increase self-confidence, increase their memorization of short letters, and are enthusiastic in religious activities